2021
DOI: 10.1007/s13410-021-00992-y
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 outbreak affected patients with diabetes mellitus?

Abstract: Background Global COVID-19 outbreak has been such a stressful experience for most of the people. Using a web-based cross-sectional study, we aimed to evaluate the acute stress response, depression, and anxiety in patients with diabetes mellitus (DM) during the COVID-19 pandemic, and to examine the effect of these psychiatric problems on diet habits and glycemic controls of patients. Methods This web-based survey of COVID-19 was sent to the patients through the Whatsapp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
(34 reference statements)
1
20
1
Order By: Relevance
“…Sisman et al . 46 reported that worsening glycemic control and an increase in dietary intake, especially carbohydrate consumption, during the COVID‐19 pandemic were related to higher anxiety and depression scores. Stress led to not only elevated BP, but also poor glycemic control 47 , 48 , and was related to various comorbidities 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Sisman et al . 46 reported that worsening glycemic control and an increase in dietary intake, especially carbohydrate consumption, during the COVID‐19 pandemic were related to higher anxiety and depression scores. Stress led to not only elevated BP, but also poor glycemic control 47 , 48 , and was related to various comorbidities 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In seven studies, drinking alcohol during the lockdown and social distancing was investigated. No increase was reported in alcohol consumption in these studies, while a reduction was reported in five studies (Olickal et al, 2020;Kishimoto et al, 2021;Sisman et al, 2021;Vetrani et al, 2021;Maruo et al, 2022), and the trend was the same in the other two studies as before the lockdown (Hansel et al, 2021;Tanaka et al, 2021). Kishimoto et al (2021) reported that 20.83% of the patients drank fewer alcoholic beverages associated with better glycemic control in them.…”
Section: Changes In Eating Habitsmentioning
confidence: 74%
“…A summary of the 22 studies eligible for review is presented in Table 1. Of the 22 studies, thirteen (59%) were cross-sectional (Ghosh et al, 2020;Khader et al, 2020;Munekawa et al, 2020;Olickal et al, 2020;Sankar et al, 2020;Carvalhal et al, 2021;Kishimoto et al, 2021;Sisman et al, 2021;Tanaka et al, 2021;Tiwari et al, 2021;Verma et al, 2021;Maruo et al, 2022;Takahara et al, 2022), and nine (41%) were cohort (Capaldo et al, 2020;Grabia et al, 2020;Jindal, 2020, 2021;Ruiz-Roso et al, 2020;Amataiti et al, 2021;Caruso et al, 2021;Hansel et al, 2021;Vetrani et al, 2021). All studies were published between 2020 and 2021.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of fears and worries were found among people with diabetes and this requires urgent interventions [ 25 ]. News media and social media platforms have played significant roles in increasing the fears and worries among people with chronic disease, especially those with diabetes [ 26 , 27 ], through amplifying their perceptions of risk. This area of investigation should be highlighted in future research…”
Section: Discussionmentioning
confidence: 99%